2018
DOI: 10.1051/e3sconf/20186803015
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors Effect Environmental Disclosure and Firm Value at Mining Companies listed Indonesia Stock Exchange

Abstract: The study aim is to examine the effect from board size, board independende, audit committee, woman on board to firm value through environmental disclosure as a mediating variable. Agency theory and stakeholder theory use in this study. The sample in this study is all mining companies listing on the Indonesian Stock Exchange. Data is the 2013-2017 from the annual report. The result shows board size and board independence to environmental disclosure not significant. However, the audit committee, woman on board e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Firms those are consistently able to implement good environmental management can have a positive impact on share prices and create a higher value of the company. This study supports previous research conducted by Plumlee et al (2015), Fuadah et al (2018), Daromes & Kawilarang (2020), and do not support Utami (2019) that environmental disclosure has not to effect on firm value.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…Firms those are consistently able to implement good environmental management can have a positive impact on share prices and create a higher value of the company. This study supports previous research conducted by Plumlee et al (2015), Fuadah et al (2018), Daromes & Kawilarang (2020), and do not support Utami (2019) that environmental disclosure has not to effect on firm value.…”
Section: Resultscontrasting
confidence: 68%
“…Plumlee et al (2015) provide evidence that the quality of environmental disclosure affects the level of firm value. Other research states that environmental disclosure and firm value show a positive relationship (Fuadah et al, 2018) and (Daromes & Kawilarang, 2020). H2: The environmental disclosure is positively related to the level of firm value.…”
Section: Environmental Disclosure and Firm Valuementioning
confidence: 94%
See 1 more Smart Citation
“…Through extensive research, it has been observed that board composition influences a company's financial performance but whether it impacts a firm's sustainable performance still remains unexplored. Higher diversity on the composition of the board and separation between chair and CEO roles reflects higher sustainable performance (Fuadah et al, 2018; Naciti, 2019). With stringent regulatory reforms on the corporate governance front, top management's decision to appoint CSE (Corporate Sustainability Executives) has caught the attention of research scholars.…”
Section: Evolution Of Research Themes Using Couplingmentioning
confidence: 99%
“…As concerns disclosure, while some studies state that the presence of female directors negatively influences sustainability disclosure (e.g. Fuadah et al, 2018) or does not impact on it (e.g. Dyduch & Krasodomska, 2017;Khan, 2010;Mousa et al, 2018), other studies find positive effects on disclosure (e.g.…”
Section: Introductionmentioning
confidence: 99%